Intravenous Granisetron Combined with Dexamethasone in Cesarean Section Patients Undergoing Spinal Anesthesia - Gaus, Syafruddin; Sjattar, Irfan Faisal; Salahuddin, Andi; Ahmad, Muhammad Ramli; Wirawan, Nur Surya; Seweng, Arifin (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Regional anesthesia, including spinal anesthesia, is the technique-of-choice over general anesthesia for cesarean section (C-section). Nausea, vomiting, and shivering are common after spinal anesthesia. Granisetron and dexamethasone are used as a premedication to prevent these reactions. AIM: This study determined the effect of different doses of granisetron combined with dexamethasone for the prevention of nausea, vomiting, and shivering. PATIENTS AND METHODS: This double-blind randomized clinical trial included patients undergoing C-section under spinal anesthesia at several hospitals in Makassar, Indonesia. Forty-five cases were divided into three equal-sized groups: G5, administered intravenous (IV) granisetron at 5 mcg/kg body weight (BW); G10, administered IV granisetron at 10 mcg/kgBW; and G25, administered IV granisetron at 25 mcg/kgBW. All patients also received IV dexamethasone at 0.1 mg/kgBW. RESULTS: In the G10 group, three cases experienced mild nausea, while, in the G5 and G25 groups, there were no incidences of nausea; this was a statistically significant difference (p = 0.043). Vomiting was not reported in any group. The G25 group had the lowest number of patients experiencing shivering (one case with a score of 3), but there were no significant differences in shivering incidence between groups (p = 0.164). CONCLUSION: Granisetron is effective in reducing nausea and shivering at certain dosage.